Exploring effective coping strategies for wives living with spouses who have alcohol dependence: Insights from focus group discussions - Jyothi Quadras; M. Anitharani; R. Johnson Pradeep (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Alcohol dependence is a prevalent issue worldwide. The wives of persons with alcohol dependence (WPAD) often experience several psychological, physical, and social problems, and it is essential to identify their coping strategies. This study aims to explore the coping strategies employed by WPAD by conducting a focus group discussion (FGD). MATERIALS AND METHODS: This study was conducted among wives of persons with alcohol dependence during their husband's admission in the departments of Psychiatry and gastroenterology of St. John's Medical College Hospital, Bangalore, India, using qualitative research with phenomenological design. The inclusion criteria were being married and living with a person with alcohol dependence for more than three years and free from major psychiatric disorders and recruited through purposive sampling for six FGDs, which were conducted using a FGD guide and lasted approximately 60 to 90 minutes. The discussions were audio-recorded and transcribed verbatim. Thematic analysis was used to analyze the data. RESULTS: The study revealed that the WPAD adhered to various coping strategies to face the challenges of living with their husbands with alcohol dependence. It is observed that WPAD used emotion-focused coping, problem-focused coping and avoidance coping. CONCLUSIONS: This study highlighted the effective coping strategies adapted by WPAD to tackle the hardships related to their husband's alcoholic behavior and most of the WPAD used emotion-focused coping. This study provided valuable insights into the coping strategies used by wives of alcoholics and the challenges they faced in managing their spouse's addiction.